First Metatarsal Proximal Opening Wedge Osteotomy for Correction of Hallux Valgus Deformity: Comparison of Straight versus Oblique Osteotomy - Han, Seung Hwan (Yonsei Med J, 2015)
PURPOSE: The aim of this study was to compare clinical and radiographic outcomes of proximal opening wedge osteotomy using a straight versus oblique osteotomy. MATERIALS AND METHODS: We retrospectively reviewed 104 consecutive first metatarsal proximal opening wedge osteotomies performed in 95 patients with hallux valgus deformity. Twenty-six feet were treated using straight metatarsal osteotomy (group A), whereas 78 feet were treated using oblique metatarsal osteotomy (group B). The hallux valgus angle (HVA), intermetatarsal angle (IMA), distal metatarsal articular angle, and distance from the first to the second metatarsal (distance) were measured for radiographic evaluation, whereas the American Orthopaedic Foot and Ankle Society (AOFAS) forefoot score was used for clinical evaluation. RESULTS: Significant corrections in the HVA, IMA, and distance from the first to the second metatarsal were obtained in both groups at the last follow-up (p<0.001). There was no difference in the mean IMA correction between the 2 groups (6.1±2.7° in group A and 6.0±2.1° in group B). However, a greater correction in the HVA and distance from the first to the second metatarsal were found in group B (HVA, 13.2±8.2°; distance, 25.1±0.2 mm) compared to group A (HVA, 20.9±7.7°; distance, 28.1±0.3 mm; p<0.001). AOFAS scores were improved in both groups. However, group B demonstrated a greater improvement relative to group A (p=0.005). CONCLUSION: Compared with a straight first metatarsal osteotomy, an oblique first metatarsal osteotomy yielded better clinical and radiological outcomes.